Предмет: Алгебра,
автор: nikailjanok201
Упростите выражения:
а) (а +2)(а-2) - а(а - 5)=
б) (b +8)(b - 6) - (b - 7)( b + 7)
Ответы
Автор ответа:
0
а) (а +2)(а-2) - а(а - 5)=a^2-4 -a^2+5a=-4+5a
б) (b +8)(b - 6) - (b - 7)( b + 7)=b^2-6b+8b-48-b^2+49=2b+1
б) (b +8)(b - 6) - (b - 7)( b + 7)=b^2-6b+8b-48-b^2+49=2b+1
Автор ответа:
0
1. a^2-2a+2a-a^2-a^2+5a=-a^2+5a
2. b^2-6b+8b-48-b^2+7b-7b-49=2b-1
но я не уверена
2. b^2-6b+8b-48-b^2+7b-7b-49=2b-1
но я не уверена
Похожие вопросы
Предмет: Химия,
автор: chuzarina
Предмет: Українська мова,
автор: riabchynskyiartem
Предмет: Русский язык,
автор: Celil
Предмет: Геометрия,
автор: Vladislav5212
Предмет: Биология,
автор: varya5555